Easier said than done? Involving citizens in the smart city. (September 2022) - Sweeting, David; de Alba-Ulloa, Jessica; Pansera, Mario; Marsh, Alex
Much of the smart cities literature urges greater citizen participation in smart city innovation. However, there is often little consideration given to how citizens might be more meaningfully involved in the processes of governance around smart cities, what enables their involvement, or what might need to change in order to facilitate their participation. Taking an institutional perspective, this paper seeks to move this aspect of the smart city debate forward. Using Mexico City as an exemplar, it examines the broader institutions of urban governance within which citizen-oriented smart city activities operate, identifying those which help and hinder citizen participation. It then considers the extent to which unhelpful institutions are embedded, and to what extent they are amenable to change to allow successful smart city participation initiatives to flourish. Our argument is that when considering citizen participation in smart city activities we need to attend more closely to the institutions which represent their context and the extent to which those institutions can be changed, where necessary, to create a more conducive environment. Many institutions will be beyond the reach of local actors to change or to deinstitutionalise; thus involving citizens in the smart city is 'easier said than done'.